2018
DOI: 10.1111/jgh.14112
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the 6‐mm fully covered self‐expandable metal stent during endoscopic ultrasound‐guided hepaticogastrostomy as a primary biliary drainage for the cases estimated difficult endoscopic retrograde cholangiopancreatography: A prospective clinical study

Abstract: The 6-mm fully covered self-expandable metal stent is safe and effective, especially for avoiding serious adverse events and allowing easy re-intervention. (UMIN000006785).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…To further examine this, a recent prospective study deployed smaller, 6 mm diameter CSEMS using the HGS method, and reported that 50% (10/20) of patients experienced obstruction due to biliary sludge (n=6) and stent dislocation (n=4). 51 Reassuringly, a new stent was successfully inserted in 9/10 cases. While this was not a direct comparison to ERCP methods, this additional data provide further support that in scenarios in which there is papillary inaccessibility or failed cannulation secondary to duodenal obstruction or altered anatomy, EUS-BD can indeed serve as a reliable salvage method, and potentially a primary modality, in managing MBO.…”
Section: Eus-bd Techniquesmentioning
confidence: 99%
“…To further examine this, a recent prospective study deployed smaller, 6 mm diameter CSEMS using the HGS method, and reported that 50% (10/20) of patients experienced obstruction due to biliary sludge (n=6) and stent dislocation (n=4). 51 Reassuringly, a new stent was successfully inserted in 9/10 cases. While this was not a direct comparison to ERCP methods, this additional data provide further support that in scenarios in which there is papillary inaccessibility or failed cannulation secondary to duodenal obstruction or altered anatomy, EUS-BD can indeed serve as a reliable salvage method, and potentially a primary modality, in managing MBO.…”
Section: Eus-bd Techniquesmentioning
confidence: 99%
“…reported usefulness of primary EUS-guided hepaticogastrostomy (EUS-HGS) for estimated difficult ERCP cases. [3] They also reported the safety of 6 mm bore fully covered metal stents. Kawakubo et al .…”
Section: Results In Published Papersmentioning
confidence: 99%
“…[7] Reintervention of EUS-BD is much easier than ERCP. [3] Ascites are commonly seen in advanced malignant patients. After pooling ascites, EUS-BD is not a safe procedure due to the possibility of infectious peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…, altered anatomy, duodenal obstruction, and previous duodenal stent) [24–28] . Okuno et al [27] published a prospective study of 20 patients undergoing EUS-guided hepa-ticogastrostomy with a 6-mm self-expanding metallic stent. The rates of technical success, clinical success, and adverse events were 100%, 95%, and 15%, respectively.…”
Section: Discussionmentioning
confidence: 99%